Photovoltaic water pumping systems based on standard frequency converters - Scortegagna, Alberto Kisner (2019)
Photovoltaic water pumping systems are commercialized as closed sets of specific components (kits) at a high cost. Nevertheless, it is possible to develop solutions based on standard components, reliable, widely available and cheaper. These solutions use standard frequency converters and AC pumps. Although it is possible to connect a high voltage photovoltaic string directly to a standard frequency converter, the string becomes oversized for low power applications, bellow several hundreds of Watts. This work develops and validates new approaches for low power applications using only up to four photovoltaic modules. The first approach uses up to 4 photovoltaic modules, charge controller, battery, battery inverter, frequency converter and a single-phase pump. The second approach uses a developed boost converter to replace the charge controller, battery and battery inverter. For the first approach, several configurations were tested based on different battery voltage levels (12, 24 and 48V) and technologies. These two approaches were validated successfully. Their results have shown that it is possible to make a system based on standard frequency converters, proving their value for small companies to develop their own cost-effective solutions due to the lower cost, modularity, and availability worldwide. This work was made in cooperation with Valled Soluções Energéticas and CHL Engenharia e Distribuição, which are small companies with experience in photovoltaic lighting and water pumping systems.